2020
DOI: 10.1155/2020/4292043
|View full text |Cite
|
Sign up to set email alerts
|

Visco‐Elastoplastic Constitutive Fatigue Model for Rocks

Abstract: The study on the constitutive fatigue model for rocks under cyclic loading has an important significance in rock engineering. In order to study the fatigue properties of rocks under cyclic loading, according to the theory of rheological mechanics and the existing three basic one-dimensional fatigue elements, i.e., elastic, viscous, and plastic fatigue elements, the three-dimensional elastic, viscous, and plastic fatigue elements were constructed. Meanwhile, a fatigue yield criterion for rocks under cyclic load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…With further research, scholars are not satisfied with only study the rock internal damage, began to build the constitutive model of rock under cyclic loading and unloading. Current research focuses on component model [17][18][19][20][21], damage fatigue constitutive model [22,23] and empirical model [24]. The constitutive model that reflects the fatigue deformation of rock is established by combining the elastic, viscous and plastic body.…”
Section: Introductionmentioning
confidence: 99%
“…With further research, scholars are not satisfied with only study the rock internal damage, began to build the constitutive model of rock under cyclic loading and unloading. Current research focuses on component model [17][18][19][20][21], damage fatigue constitutive model [22,23] and empirical model [24]. The constitutive model that reflects the fatigue deformation of rock is established by combining the elastic, viscous and plastic body.…”
Section: Introductionmentioning
confidence: 99%
“…Many slopes became unstable and landslides happened in June 2003 when the reservoir level rose to 135 m [1]. After its completion in 2009, the reservoir water level fluctuates sporadically between 145 m and 175 m. In reservoir area more than 2000 landslides are reported that are strongly or partially affected by the water storage [2][3][4][5][6]. The survival of local residents and property is threatened by potential landslide instability.…”
Section: Introductionmentioning
confidence: 99%